1996
DOI: 10.1111/j.1365-2516.1996.tb00027.x
|View full text |Cite
|
Sign up to set email alerts
|

Disarticulation of a knee joint in a haemophiliac with high inhibitor titre

Abstract: Disarticulation of a knee joint in an 8-year-old haemophilia A patient with high inhibitor of 3450 Bethesda units (BU) is described. He had an infected compound fracture of the tibia and fibula. Surgery was successfully performed after extensive plasma exchange; administration of immunosuppressive agents such as cyclophosphamide, methylprednisolone, intravenous immunoglobulin and cyclosporine were combined with a loading dose of 100 units kg(-1) of factor VIII concentrate, followed by continuous infusion of 16… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 7 publications
(1 reference statement)
0
6
0
Order By: Relevance
“…The successful disarticulation of the knee joint was previously reported in 1996 [8]. At 8 years of age, he had an infected compound fracture of both the tibia and ®bula and exhibited the highest inhibitor titre of 3450 BU.…”
Section: Case Reportmentioning
confidence: 78%
See 1 more Smart Citation
“…The successful disarticulation of the knee joint was previously reported in 1996 [8]. At 8 years of age, he had an infected compound fracture of both the tibia and ®bula and exhibited the highest inhibitor titre of 3450 BU.…”
Section: Case Reportmentioning
confidence: 78%
“…At 8 years of age, he had an infected compound fracture of both the tibia and ®bula and exhibited the highest inhibitor titre of 3450 BU. The successful disarticulation of the knee joint was previously reported in 1996 [8]. He walked using crutches and an arti®cial leg.…”
Section: Case Reportmentioning
confidence: 99%
“…Haemophiliac treatment and medication in less developed countries are far behind those in more developed countries. Moreover, the management of bleeding in haemophiliacs with inhibitors is more difficult due to limited supplies of blood products such as prothrombin complex concentrate, factor VIII concentrate and recombinant activated factor VII (rFVIIa) [1]. Recently, several studies have shown the efficacy of rFVIIa in controlling bleeding episodes [2,3].…”
Section: Patients Receiving Rfviia For Controlling Bleeding Episodesmentioning
confidence: 99%
“…In cases of life-saving conditions among patients with severe bleeding episodes, plasma exchange was performed before bolus administration of factor VIII or IX concentrate accordingly. [9][10][11][12] Bypassing agents of rFVIIa and aPCC [13][14][15][16] have been available in 2000 and 2003, respectively.…”
mentioning
confidence: 99%